State Boredom Partially Accounts for Gender Differences in Novel Lexicon Learning - Wang, Hua; Xu, Yong; Song, Hongwen; Mao, Tianxin; Huang, Yan; Xu, Sihua; Zhang, Xiaochu; Rao, Hengyi (Frontiers in Psychology, 2022)
Gender plays an important role in second language acquisition and females typically do better than males during lexicon learning. Recent studies suggest that boredom as negative emotion may impair language learning and females are less likely to experience boredom than males. However, the contribution of boredom to gender differences in lexicon learning remains unclear. To address this question, in this study we conducted two experiments with a large cohort of over 1,000 students to explore the relationships between gender differences in boredom and lexicon learning. In Experiment 1, a cohort of 527 participants (238 males) completed the trait and state boredom scales as well as a novel lexicon learning task without awareness of the testing process. In Experiment 2, an independent cohort of 506 participants (228 males) completed the same lexicon learning task in the condition of knowing the testing procedure a priori. Results from both experiments consistently showed significant gender differences in the word forgetting rate and state boredom scores, with females doing better than males. Furthermore, differences in state boredom partially explained differences in word forgetting rate between females and males. These findings demonstrate a novel contribution of state boredom to gender differences in lexicon learning which provide new insights into better language learning ability in females.